The Role of Local Communities in the Discourse of Controversial Heritage of Norway and Estonia - Ave Paulus; Arnstein Bard Brekke (Ochrona Dziedzictwa Kulturowego)
This chapter analyses paradigm shifts in the discourse of heritage sites connected with tragic personal stories, memories and relics, emphasising local communities’ role in reframing controversial heritage in Norway and Estonia. Although these stories come from different cultures and places, they all revolve around the question of how we approach the most delicate strings in the human mind: beliefs, sorrows and dignity. The sites under discussion are “ hosts” of tragedies from the past century. Among heritage communities, states and experts, there were intense debates about the value and fate of those areas. Besides several historical, political and socioeconomic issues, personal wounds weretaken into account. The ﬁrst case describes initatives of heritage communities to recognize and acknowledge values of contested Cold War heritage: Suurpea Naval Base built during Soviet occupation, and the deportations on the coasts of Estonia. The second case deals with the initial demolition and later recognition of Sami burial sites and sacred landscapes of Arctic Norway, restoring rights to Saami heritage. These cases highlight the importance of inclusiveness in dealing with conﬂicting histories, involoving reconciliation and restitution of dignity to the heritage and communities concerned. Authors rely on a holistic concept of cultural heritage. Community spirit and and sense of place are essential indicators of local character. Authors show the beneﬁts of a people-centred approach towards heritage as a basis for transformative change in heritage protection. The authors’ positions are not purely academic as they have been involved in deﬁning and protecting the cultural heritage in discussed areas.